The Europe We Want. Issue 2 (September 2016) - Strohschneider, Peter
Abstract: Research policy and research funding must not be allowed to lapse into the thought patterns that are currently gaining ground throughout the continent. Research and innovation for a Europe fully equipped for the challenges of tomorrow should be based not on economistic reductionism but solely on pluralism and freedom.